Sociological diagnostics of public administration by the higher education system in the Republic of Kazakhstan - Bugubayeva, R.O.; Tapenova, G.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the interaction of subjects in the management of higher education system is considered, the effectiveness of public administration and the implementation of state policy in the system of higher education is evaluated. A sociological diagnosis was carried out to study the opinions of managers and specialists in higher education about the level of public administration of the education system and ways to improve it. A comprehensive analysis of the current state of management was made, the significance of quantitative and qualitative methods of sociological diagnostics as a tool for assessing the effectiveness of public administration in the higher education system is substantiated. A number of reasons for dissatisfaction, or partly respondents' satisfaction with state administration of the higher education system, have been identified. The authors made suggestions for solving the problems of graduates' employment after graduation, housing problems and supporting in higher education.